2021
DOI: 10.51245/rijbr.v6i1.2021.244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Behavioral Biases on Investment Decisions: Moderating Effect of Preferred Sector of Investment

Abstract: The study aims to recognize the behavioral biases that influence the decisions making process and investment decisions of retail investors while investing in stocks of insurance and pharmaceutical sector stocks. The paper also aims at checking the moderating effect of the preferred sector of investment on these relationships. The conceptual model derived from past literature was checked for its reliability and validity, using measurement model assessment and structural model assessment. Hypothesis or the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…This research problem employed the use of partly Descriptive and partly Conclusive/ Causal. Tahir Imran Gulzar, Dr. Najabat Ali [2] study focuses on examining the impact of six behavioral biases (availability bias, self-control bias, overconfidence bias, illusion of control bias, and representative bias) on investment decisions. The findings of the study indicate that the variables under investigation explain 37.53% of the overall variance, suggesting that there are no significant issues with the chosen methodology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research problem employed the use of partly Descriptive and partly Conclusive/ Causal. Tahir Imran Gulzar, Dr. Najabat Ali [2] study focuses on examining the impact of six behavioral biases (availability bias, self-control bias, overconfidence bias, illusion of control bias, and representative bias) on investment decisions. The findings of the study indicate that the variables under investigation explain 37.53% of the overall variance, suggesting that there are no significant issues with the chosen methodology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aside from the influencers identified by Acquah-Sam (2014), studies within other developing countries (Babajide and Adetiloye, 2012;Khawaja et al, 2013;Gupta and Ahmed, 2017) have identified behavioural biases as a significant influencer of capital markets. These studies, however, focus on stock markets and so fail to explain how various behavioural biases impact or affect the performance of the mutual fund markets in those countries.…”
Section: Introductionmentioning
confidence: 99%
“…The intentions towards desiring an investment are driven by enumerable factors. When making investment decisions, investors can be biased (Gupta et al 2021). Rational investors are very aware of optimized decisions which is a part of their decision making.…”
Section: Introductionmentioning
confidence: 99%